“Europa in de Tropen”, The Colonial Tourism and Urban Culture in Bandung - Rahmia Nurwulandari; Kemas Ridwan Kurniawan (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2020)
Bandung experienced a rapid urban development after 1918, when the city was prepared to be the new Dutch East Indies’ capital city, replacing Batavia. In the era of economic liberalization, Bandung also became one of the tourist destinations that has promoted by the businessmen. This paper is a study on how mass tourism as the new urban culture in the beginning of 20th century had a contribution to urban planning in Bandung. The timeline was after the establishment of train as a modern transportation in Bandung (1884) until the end of the Dutch Colonialism in Dutch East Indies (1942). Through the Georg Simmel's theory of sociology and the city, I tried to analyze the the tourism activity and its relations to the 20th century urban architecture in Bandung, West Java. I use the method that was introduced by Iain Borden and friends in The Unknown City to understand tourism and urban history of Bandung through the spatial practice, city representation and experiences.